Potential protective effects of tualang honey and Ficus deltoidea dack var.deltoidea against bisphenol a induced toxicity in the reproductive system of pre-pubertal female rats / Siti Sarah Mohammad Zaid - Siti Sarah, Mohammad Zaid (2016)
Bisphenol A (BPA) is one of the most ubiquitous environmental endocrine disrupting chemicals that can disrupt the normal development and functions of the female reproductive system. In the last few decades, considerable amount of evidence has shown that young women are put at high risk of reproductive infertility from their routine exposure to numerous BPA-products since BPA induces increased production of reactive oxygen species (ROS), which is responsible for reducing the levels of endogenous antioxidant enzymes and increasing the levels of lipid peroxides. Thus, natural products containing high antioxidant properties such as tualang honey (Malaysian wild local honey) and Ficus deltoidea (Malaysian local herbal plant), were selected to study their possible potentials to counter the detrimental effects of BPA on the female reproductive system. The objective of the present study was to investigate the potential protective effects of Tualang honey and Ficus deltoidea against BPA-induced toxicity in the female reproductive system of prepubertal female Sprague Dawley rats. Animals were divided into six groups (n=8 in each group) that consist of (i) control group (received corn oil), (ii) BPA-exposed group (received BPA), (iii) TH+BPA group (received Tualang honey before receiving BPA), (iv) TH control group (received Tualang honey alone), (v) FD+BPA group (received Ficus deltoidea before receiving BPA) and (vi) FD control group (received Ficus deltoidea alone). The administration of the various treatment agents was performed once daily by oral gavage for six consecutive weeks. Uterine and ovarian toxicity of BPA-exposed rats were evident from the changes in the estrous cycle, disruption in the gonadotropins hormone levels (FSH and LH), follicular development and secretion of sexual steroid hormones (17β-estradiol and progesterone) by the ovary. BPA toxicity also results in disruptive effects on the uterus by inducing morphological abnormalities, increasing oxidative stress and dysregulating the expression and iv distribution of the estrogen sensitive genes, ERα, ERβ and C3. Pretreatment with Tualang honey and Ficus deltoidea in the BPA-exposed rats showed significant protection on the reproductive system as shown by the increase in the percentage of rats with normal estrous cycle, increase in the level of gonadotropins hormone (FSH), reduction in the formation of the atretic follicles and normalization of the progesterone secretion by the ovary. In addition, there was lesser degree of abnormalities in the uterine and ovarian morphology and reduced disruptions at the transcriptional and translational levels of ERα, ERβ and C3, as well as reducing lipid peroxidation and subsequently the level of oxidative stress within the uterus. More importantly, there were no obvious estrous cycle, morphological, hormonal, as well as expression and distribution of ERα, ERβ and C3 changes observed in rats treated with Tualang honey and Ficus deltoidea alone. In conclusion, we suggest that Tualang honey and Ficus deltoidea have the potential protective role to counter the toxicity effects of BPA on the female reproductive system, possibly by their phytochemical properties, and further future studies can be conducted to determine the mechanisms involved in such activities.